Penerapan Teknik Cording Pada Busana Pesta Dengan Sumber Ide Menara Lonceng Venesia - Icha Riga Ayuni; Ratna Suhartini (Universitas Negeri Surabaya, 2025)
The Venetian Bell Tower, or Campanile de San Marco, served as the main inspiration for designing men’s and women’s evening wear through the application of the surface cording decorative technique. This study aims (1) to describe the application of cording in evening wear inspired by the architectural details of the Campanile, and (2) to examine the design process and final results. The research employed the Double Diamond model consisting of four stages: discover, define, develop, and deliver. In the discover stage, the architectural inspiration was explored, followed by the define stage where ideas were summarized into a moodboard. The develop stage produced two selected designs, one for men and one for women, while the deliver stage focused on garment realization with input from experts. The results show that architectural forms such as strong lines and relief details of the Campanile can be transformed into ornamental fabric design using surface cording. The technique creates raised textures that highlight both aesthetic and functional aspects, enhancing the garment’s visual identity. Overall, the study demonstrates that cording not only enriches fabric texture but also elevates the artistic and conceptual value of evening wear design.